ANALISI HUBUNGAN DERMATITIS KONTAK DENGAN MASA - Novrian Agung; Mochammad Nur Ridho Ozim (Universitas Airlangga, 2024)
Background: Contact dermatitis is a skin inflammation caused by exposure to irritants or allergens, often associated with occupational exposure. Its causes include endogenous factors, such as genetics and atopic history, as well as exogenous factors, such as chemical properties and exposure duration. This condition has a high global prevalence, particularly in tropical regions. In Indonesia, dermatitis ranks third among the top ten skin diseases, with most cases being work-related. Contact dermatitis is classified into Irritant Contact Dermatitis (ICD) and Allergic Contact Dermatitis (ACD), with risk factors including exposure duration, use of Personal Protective Equipment (PPE), and history of skin diseases. High-risk industries include manufacturing, construction, and printing. Objective: Analyzing the factors of work duration and history of atopy that contribute to the risk of contact dermatitis among workers at the hand-rolled cigarette factory Mitra Produksi Sigaret Koperasi Unit Desa (MPS KUD) Tani Mulyo, Lamongan. Method: The study is an analytical research with a cross-sectional study design. Bivariate analysis was conducted using the chi-square test and the Mann-Whitney U test. The sampling technique used was total sampling, with the study population consisting of all production workers at a hand-rolled cigarette factory in Turi District, Lamongan Regency, in 2022. The total sample size was 81 participants. The analysis instruments used included questionnaires, medical examination sheets, and observation sheets. Results: The results of this analysis show that 49 individuals (60.5%) experienced contact dermatitis among hand-rolled cigarette production workers, with the most common cause being endogenous factors related to individual susceptibility. The analysis also demonstrates that the variables significantly associated with contact dermatitis are a history of atopy (p=0.000) and length of employment (p=0.000). Conclusions: This analysis proves that there is a significant association between atopy history and length of service with the incidence of contact dermatitis in workers at MPS KUD Tani Mulyo. These findings emphasise the need for special prevention and protection efforts for high-risk workers, especially those with a history of atopy and a long working life.